2020
DOI: 10.36941/mjss-2020-0039
|View full text |Cite
|
Sign up to set email alerts
|

Academic Staff Perception of the Extent of Politicizing Administration of Universities: Implications for National Development

Abstract: The aim of this study was to examine academic staff perception of the extent of politicizing administration of universities: Implications for National Development. The study adopted survey research design. The study was guided by two research questions and two research hypotheses. The population of the study was made up of all academic staff in the University of Calabar and Cross River University of Technology, all in Cross River State, Nigeria. Out of the sample size of 430 academic staff used for the study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…The outcome of this study is not surprising because politics is pervasive and cannot be avoided in the management of university education. This result is in line with Edet et al (2020) who found among others that administrative processes in terms of allocation of courses to the lecturers, methods of offer of appointment in recent time, appointment of principal, officers within the university, appointment of membership into various committees within university, appointment of academic advisers, office of the HODs, Deanship position, award of research grants, award of Honorary Degrees by Universities to political office holders and academic staff promotion criteria are highly politicized within the universities.…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 3 more Smart Citations
“…The outcome of this study is not surprising because politics is pervasive and cannot be avoided in the management of university education. This result is in line with Edet et al (2020) who found among others that administrative processes in terms of allocation of courses to the lecturers, methods of offer of appointment in recent time, appointment of principal, officers within the university, appointment of membership into various committees within university, appointment of academic advisers, office of the HODs, Deanship position, award of research grants, award of Honorary Degrees by Universities to political office holders and academic staff promotion criteria are highly politicized within the universities.…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…To achieve educational predetermined goals, all educational activities and programmes are done under a given governance (Edet, Asuquo and Okon (2020). Governance are the values and rules through which public affairs are managed in a manner that is transparent, participatory, inclusive and responsive (Ogbodo, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to the authors, it would be a bad idea to rely solely on one source of funding for universities since it would pose problems with the budgetary allocation for education in the event of a change in government. In agreement with Akindutire, Ayodele Osiki and Edet et al (2020) claims that politics exists within all associations and organisations, formal and informal, as well as among political parties that control governmental policy at the local, state, and federal levels. This shows that politics permeates every aspect of most organisations and influences the choices that are made there.…”
Section: Politicsmentioning
confidence: 92%